Parenting Practices and Religious Character Development in Early Childhood: A Study of Tanjung Morawa Village - Izzatunnisa, Yasmin; Mutiawati, Mutiawati (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2024)
Religious character development is a coaching effort provided by parents to their children, typically initiated at an early age to instill religion and its values as a means of training and developing children to possess good morals, obedience in worship, and noble attitudes and traits both in the present and future. This research aims to investigate the parenting or parenting practices employed in children's lives to foster religious character. The focus of this study is to describe the nurturing and coaching provided by parents to their children as educators in a family setting to form a religious character. This research utilizes a qualitative method with a descriptive approach and is conducted in Tanjung Morawa-A Village. The subjects of the research are parents of early childhood aged 4-6 years. The data collection techniques employed include interviews, observation, and documentation. The data analysis employs Miles and Huberman's method, which involves data reduction, data presentation, and conclusion drawing. The results of this study indicate that parents in Tanjung Morawa-A Village utilize democratic parenting practices in fostering their children's religious character from an early age. Parents employ various strategies to foster their children's religious character, including providing religious education, incorporating religious values in everyday life, setting good examples, and offering advice. The success of the parenting strategies implemented by parents in Tanjung Morawa Village is evidenced by their children's development of noble character traits, such as politeness, honesty, good behavior, and good words, as well as their knowledge of Allah SWT, His Messenger, and His teachings.